La guerre en Afghanistan : portée, forces et faiblesses du concept de culture de guerre appliqué aux guerres modernes - Aycha Fleury (Amnis, 2011)
The aim of this article is to analyze the range, the strengths and weaknesses of the concept of «war culture» as it is applied to the war in Afghanistan. The constructivist theory used in social sciences permits to comprehend the social constructions behind a culture of war and its four dimensions: violence, hatred, consent to warfare and religious zeal. The war in Afghanistan is a new war, typical of changes that occur in peace keeping missions. This concept of «war culture» permits us to comprehend certain quite specific aspects of the problems that surround this new warfare. The conflict in Afghanistan also demonstrates the limits of this approach, notably the lack of a «temporal» factor and the absence of consideration of the historical construction of the conflict in Afghanistan. In conclusion, the concept of «war culture» is not sufficient to fully capture the complexity of a conflict like the one in Afghanistan, yet it does permit new perspectives of analysis as well as permits to defeat some facts erroneously taken for granted.